A construção da textualidade no gênero regras de jogo em produções orais de crianças da pré-escola - Medeiros, Neilson Alves de (2009)
This paper aims to describe how the process of acquisition of oral genre game rules occurs in children from pre-school focusing on the construction of textuality. To do so, we collected data from a classroom of Childhood Education, with children of 4 years old, that elaborate their oral texts. The events listed are developed within activities of a didactic sequence, whose main goal is the teaching of oral genre 'game rules'. For data analysis, we adopted the principles of textuality (cohesion, coherence, intentionality, acceptability, situationality, informativity and intertextuality) as well as the characteristics of the oral genre 'game rules'. In analyzing the data, we observed that the entrance of the child in the genre studied presentes evidences related to the principles of textuality, and the construction of this phenomenon is not equal for all children. Besides that, data point that, to learn the 'game rules', other oral genres come into play as intermediary instruments in this process.